Induction of Multiple Immune Regulatory Pathways with Differential Impact in HCV/HIV Coinfection - Cho, Hyosun; Kikuchi, Masahiro; Li, Yun; Nakamoto, Nobuhiro; Amorosa, Valerianna K.; Valiga, Mary E.; Chang, Kyong-Mi (Frontiers in Immunology, 2014)
Persistent viral infections including HCV, HBV, and HIV are associated with increased immune regulatory pathways including the extrinsic FoxP3+CD4+ regulatory T cells (Tregs) and intrinsic inhibitory pathways such as programed death-1 (PD-1) and cytotoxic T lymphocyte antigen-4 (CTLA-4) with potentially reversible suppression of antiviral effector T cells (1–12). Immunological consequences of viral coinfections relative to these immune regulatory pathways and their interplay are not well-defined. In this study, we examined the frequency, phenotype, and effector function of circulating T cell subsets in patients with chronic HCV and/or HIV infection, hypothesizing that HCV/HIV coinfection will result in greater immune dysregulation with pathogenetic consequences (13, 14). We show that multiple T cell inhibitory pathways are induced in HCV/HIV coinfection including FoxP3+ Tregs, PD-1, and CTLA-4 in inverse association with overall CD4 T cell frequency but not with liver function or HCV RNA titers. The inverse association between CD4 T cell frequency and their FoxP3, PD-1, or CTLA-4 expression remained significant in all subjects combined regardless of HCV and/or HIV infection, suggesting a global homeostatic mechanism to maintain immune regulation relative to CD4 T cell frequency. PD-1 blockade rescued T cell responses to HIV but not HCV without significant impact by CTLA-4 blockade in vitro. Collectively, these findings highlight complex immune interactions in viral coinfections and differential regulatory pathways influencing virus-specific T cells that are relevant in immunotherapeutic development.